Sex matters: Gender differences in a professional setting - Alexandra Niessen; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2007)
This paper shows that gender di®erences exist in a professional setting where man-agers have a similar educational background and work experience. Using data from the U.S. mutual fund industry we find that female managers are more risk averse, follow less extreme and more consistent investment styles and trade less than male managers. Although female and male managers do not differ in average performance, female man-agers receive significantly lower inflows. This suggests that they might be stereotyped as less skilled. Furthermore, they mainly work in companies that are large, well established and that are located in less conservative states of the U.S.
Keywords: G23; J2; J71; 330; Gender Di®erences; Mutual Funds; Risk Aversion; Stereotyping